Tensorflow vs R: A Comparative Study of Usability - Dias, Luís; Neto, Rosalvo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6093, 2017)
Google released on November of 2015 Tensorflow, an open source machine learning framework that can be used to implement Deep Neural Network algorithms, a class of algorithms that shows great potential in solving complex problems. Considering the importance of usability in software success, this research aims to perform a usability analysis on Tensorflow and to compare it with another widely used framework, R. The evaluation was performed through usability tests with university students. The study led do indications that Tensorflow usability is equal or better than the usability of traditional frameworks used by the scientific community.